An assessment of the gender gap in African agricultural research capacities - Beintema, Nienke M. (2017)
Female researchers offer different insights from their male counterparts, and their input provides an important perspective in addressing the unique and pressing challenges of female farmers. Consequently, it is important that agricultural research agencies employ a balance of male and female researchers. Statistics on sex-disaggregated capacity trends are needed to enable decision-makers to set priorities and benchmarks and to monitor progress. New evidence collected through Agricultural Science and Technology Indicators(ASTI) shows that the gender gap in African agricultural research, although still substantial, continued to decline. In some countries, however, the participation of women in agricultural research continues to be extremely low. Furthermore, female researchers are often young and less qualified than their male colleagues. Although the ASTI evidence provides some useful insights, this article argues that more detailed information is needed to ensure that gender issues are better and more effectively taken into consideration in policy formulation for and implementation of agricultural research issues.